THE NEGATIVE SIDE OF GLOBALIZATION AND NEOLIBERALISM: PRECARIAT AS A NEW PHENOMENON - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The paper on the basis of the works of Western scholars considers a new social phenomenon of the globalization era and a flexible labor market, namely the "precariat". It clarifies its structure, causes of formation, especially social feelings and consciousness as well.